Inhaled nitric oxide for a severe respiratory syncytial virus infection in an infant with bronchopulmonary dysplasia - Leclerc, F. (Intensive Care Med, 1994)
OBJECTIVE: To report the first case of ARDS in children treated with nitric oxide (NO) inhalation. METHODS: A 13-months infant presented with BPD and severe hypoxemia related to RSV infection and ARDS. Inhaled NO was delivered in the ventilatory circuit of a continuous flow ventilator (Babylog 8000, Dräger) in a concentration of 20–80 ppm for 7 days. NO and NO(2) were continuously monitored (Polyton Draeger). Respiratory mechanics were evaluated by using the method of passive inflation by the ventilator. RESULTS: NO inhalation improved oxygenation (tcSaO(2)) and reduced respiratory system resistance without affecting arterial pressure. NO(2) level remained below 5 ppm, and methaemoglobin level below 1%. The child survived without neurologic sequela. CONCLUSIONS: Two mechanisms to explain oxygenation improvement can be suggested:selective improvement in perfusion of ventilated regions and bronchodilation.